2018
DOI: 10.4103/ijp.ijp_65_17
|View full text |Cite
|
Sign up to set email alerts
|

Gas chromatography coupled to mass spectrometry characterization, anti-inflammatory effect, wound-healing potential, and hair growth-promoting activity of Algerian Carthamus caeruleus L (Asteraceae)

Abstract: OBJECTIVES:The roots of Carthamus caeruleus have been used by the population of Northern Algeria to treat several pathological conditions, including wound healing and hair growth. The present study was conducted to evaluate the anti-inflammatory activity, wound-healing potential, and hair growth-promoting activity attributed to C. caeruleus root.MATERIALS AND METHODS:In this study, we have investigated the anti-inflammatory effect using carrageenan-induced paw edema test, evaluated the wound-healing potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
2
5
0
Order By: Relevance
“…Results in this study show a very important granuloma in histological slides of carrageenan control group, the treatment with Carthamus caeruleus L has shown a minimal inflammatory granuloma. Our results are in the same order with Dahmani et al (2018) , Benhamou et al (2013 and Benmansour et al (2020) with Carthamus caeruleus L collected from Tizi Ouzou , Setif and Tipaza, respectively. They have shown that the rhizomes of this herb were effective against inflammation induced by carrageenan in experimental animals.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Results in this study show a very important granuloma in histological slides of carrageenan control group, the treatment with Carthamus caeruleus L has shown a minimal inflammatory granuloma. Our results are in the same order with Dahmani et al (2018) , Benhamou et al (2013 and Benmansour et al (2020) with Carthamus caeruleus L collected from Tizi Ouzou , Setif and Tipaza, respectively. They have shown that the rhizomes of this herb were effective against inflammation induced by carrageenan in experimental animals.…”
Section: Discussionsupporting
confidence: 90%
“…Our results of phytochemical screening are in the same order with the results of Dahmani et al (2018) and Benhamou et al (2013) with Carthamus caeruleus L collected from Tizi Ouzou and Setif regions respectively in Algeria; they found that the rhizomes of this plant are rich in tannins, anthocyanins, flavonoids, leucoanthocyanins, saponins, terpenoids and steroids, glycosides, mucilage, and coumarins. The results show that the total polyphenols compounds in rhizome aqueous crude extract of Carthamus caeruleus L was low 13.08 ±0.22 mg GAE/g DM as well as flavonoids with 5.02 ±0.55 mg EQ / g DW.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The anti-inflammatory and anti-nociceptive effect of plants has been attributed to their secondary metabolites such as flavonoids, saponins, steroids, terpenoids, tannins and alkaloids (Birhane et al, 2020). The phytochemical studies on the rihzomes of Algerian Carthamus caeruleus L with gaz chromatography coupled to the mass spectroscopy were carried out by Dahmani et al (2018) and Benhamou et al (2013) who showed the presence of sesquiterpenes and fatty acids such as palmitic acid and mono(2-ethylhexyl) phthalate (MEHP) and 5-(hydroxymethyl)-2furancarboxaldehyde . Many pharmacological studies on active plant components showed that unsaturated fatty acids like palmitic acids are able to influence the biochemical properties of the membrane such as fluidity and permeability (Dhifi et al, 2013;Nasri et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%